Etnolingual Mappalili: Analisis Lanskap Linguistik dalam Pelestarian Tradisi Agraris Bugis - Karmila Karmila; Andi Muhammad Irfan Taufan Asfar; Andi Muhammad Iqbal Akbar Asfar (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2026)
The Mappalili tradition represents an important component of Bugis agrarian culture that preserves linguistic expressions alongside the community’s cultural identity. This study aims to analyze the linguistic elements embedded in the Mappalili tradition, examine the linguistic structures of its prayers and ritual chants, and explore their symbolic meanings and cultural values. The research employed a mixed-method approach by integrating quantitative and qualitative techniques. Data were collected through questionnaires administered to 133 respondents, in-depth interviews with community leaders and farmers, and participant observation. Quantitative data were analyzed using SPSS, while qualitative data were examined with ATLAS.ti to identify linguistic patterns and cultural themes. The findings demonstrate that Mappalili embodies diverse linguistic components, including phonological, morphological, syntactic, semantic, and pragmatic features, which are closely intertwined with the agrarian, religious, and social values of the Bugis community. The study argues that Mappalili serves not only as a cultural ritual but also as a significant medium for preserving and revitalizing the classical Bugis language through educational initiatives and culturally oriented language preservation policies.